2004
DOI: 10.1049/el:20040068
|View full text |Cite
|
Sign up to set email alerts
|

Efficient block size selection in H.264 video coding standard

Abstract: This letter aims at selecting an efficient variable block size mode in H.264 video coding standard for better compression performance. The proposed scheme is based on 3D Recursive Search algorithm and takes into account the motion vector cost and previous frame information. The best mode for the current macroblock is obtained by analyzing the modes for a maximum of four macroblocks in the current and the previous frames. An improvement in the encoding time with negligible impact on the subjective and the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…where f (m, n) represents the current sub-block of N 2 pixels at coordinates (m, n) and f (m + i, n + j) represents the corresponding block in the previous frame at new coordinates (m + i, n + j) Choosing large block size is computationally efficient but it results in the poor quality of the reconstructed frame so we choose block size as 8 × 8 as a tradeoff between computational complexity and the quality of the image [20]. The maximum displacement of block in horizontal and vertical direction is assumed to be …”
Section: Resultsmentioning
confidence: 99%
“…where f (m, n) represents the current sub-block of N 2 pixels at coordinates (m, n) and f (m + i, n + j) represents the corresponding block in the previous frame at new coordinates (m + i, n + j) Choosing large block size is computationally efficient but it results in the poor quality of the reconstructed frame so we choose block size as 8 × 8 as a tradeoff between computational complexity and the quality of the image [20]. The maximum displacement of block in horizontal and vertical direction is assumed to be …”
Section: Resultsmentioning
confidence: 99%
“…This can improve the prediction and results in better compression rates, but at the cost of increasing computational complexity. Several variable block-size selection algorithms have been proposed to reduce the encoding time, such as the signal to noise ratio (SNR)-based algorithm [7,8], adaptive threshold cost-based algorithm [7,8], 3D recursive search scheme-based algorithm [7,8], and the complexity measurement-based algorithm [9]. …”
Section: 1mentioning
confidence: 99%
“…A real-time codec is required to encode and decode a bit-stream as soon as a frame becomes available thus subjecting significant computational constraints on the underlying computing platform. A lot of research work has recently been reported [1][2][3][4] that addresses complexity reductions in video encoders. Most of the existing work concentrates on development of fast algorithms for various modules of the encoder.…”
Section: Introductionmentioning
confidence: 99%